Neuroeducational Assessment Design of Islamic Religious Education in the Era of Society 5.0 - Raniya, Pudyas Tataquna; Silmi, Thoriq Aji; Kusaeri, Kusaeri; Suparto, Suparto; Malyuna, Sita Isna (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study designs a neuroscience-based Islamic religious education assessment in the era of society 5.0 that combines neuroscience and learning evaluation to assess cognitive, affective, and psychomotor aspects. Using a Systematic Literature Review (SLR) approach with PRISMA methodology, this study synthesized findings from 23 articles published between 2014 and 2025. The PRISMA approach was used for data analysis, which is a systematic review that aims to screen, evaluate, and report the literature transparently. The steps of data analysis with PRISMA involved a process of identification, screening, feasibility assessment, and inclusion of relevant literature. The results of this study compiled a neuroscience-based neuroeducational assessment design in Islamic education learning based on Paul D. Maclean's theory (triune brain), which is expected to contribute to assessment innovation in Islamic education to answer the needs of the learning process that is relevant to the challenges and potential of society 5.0.